Hard Currency Prices and Industrial Equity market Indices: Impact Study in Indonesia Stock Exchange - Pasaribu, Benhard Martin; Nugroho, Anggoro Budi (Journal of Business and Management, 2014)
An exchange rate is the rate where a currency can be exchanged with another currency from different country. For years, people have been tried to find the relationship between exchange rates and stock market. There are some reasons for that, first, it will be a factor to determine decisions about monetary and fiscal policy because exchange rate play vital role in a countryÃ¢â‚¬â„¢s level of trade. Second, with knowing the relation between both of them, we can predict futureÃ¢â‚¬â„¢s decision in the stocks market by analyzes the situation of current exchange rates condition in Indonesia. Last, understand the exchange rate-stock market relationship can help the government to mitigate crisis. This paper aims to determine how currency fluctuations affect the business sector through the Industrial index. Currencies that the author uses for this research are 5 Hard Currency, which are US Dollar, Euro, Pound sterling, Japanese Yen, and Australian Dollar. Hard Currency is any currency that is expected to serve as a reliable and stable store of value. For the Industrial Index, author use 10 sectors which are classified in the Indonesian Stock Exchange (IDX). They are agriculture, mining, industrial base and chemical, various industries, consumer goods, property and real estate, infrastructure and utilities, finance, trade, and manufacture.Keywords: Hard Currency, Stock Market, Industrial Indices, Indonesia, and RelationÃ‚Â